#### Answer

y=1

#### Work Step by Step

Simplifying
-5y + 12 = 12y + -5
Reorder the terms:
12 + -5y = 12y + -5
Reorder the terms:
12 + -5y = -5 + 12y
Solving
12 + -5y = -5 + 12y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-12y' to each side of the equation.
12 + -5y + -12y = -5 + 12y + -12y
Combine like terms: -5y + -12y = -17y
12 + -17y = -5 + 12y + -12y
Combine like terms: 12y + -12y = 0
12 + -17y = -5 + 0
12 + -17y = -5
Add '-12' to each side of the equation.
12 + -12 + -17y = -5 + -12
Combine like terms: 12 + -12 = 0
0 + -17y = -5 + -12
-17y = -5 + -12
Combine like terms: -5 + -12 = -17
-17y = -17
Divide each side by '-17'.
y = 1
Simplifying
y = 1